2010
DOI: 10.1177/000348941011901114
|View full text |Cite
|
Sign up to set email alerts
|

Role of Reflux in Tracheoesophageal Fistula Problems after Laryngectomy

Abstract: Objectives The purpose of this 2-year prospective nonrandomized study was to investigate the relationship between pathological supraesophageal reflux and the occurrence of speech fistula complications, especially severe fistula enlargement, in patients who underwent total laryngectomy and prosthetic voice restoration. Methods We objectively assessed the presence of reflux disease using 24-hour dual-probe pH monitoring in 60 laryngectomized patients, correlated the incidence of tracheoesophageal fistula complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 25 publications
(5 reference statements)
2
15
0
1
Order By: Relevance
“…One hundred twenty patients (83%) had a postoperative complication (major or minor), including those that were directly related and those that were not related to the TEP (Table ) . Eighty‐nine patients (61%) had 2 or more complications.…”
Section: Resultsmentioning
confidence: 99%
“…One hundred twenty patients (83%) had a postoperative complication (major or minor), including those that were directly related and those that were not related to the TEP (Table ) . Eighty‐nine patients (61%) had 2 or more complications.…”
Section: Resultsmentioning
confidence: 99%
“…4 This figure compares favorably with the 12% after 1 year in a recent study from Germany. Especially of interest in this respect is the study of Lorenz et al, 25 where these authors found that device lifetime was significantly associated with reflux. This concerns the role of the special problem-solving VPs Provox ActiValve Light and Strong in comparison to the regular VPs (Provox2 and Vega).…”
Section: Discussionmentioning
confidence: 99%
“…Laryngectomy results in changes in pharyngeal plexus innervation and in esophageal motility; a pressure decrease at the level of the upper esophageal sphincter has been observed . Reflux is also recognized as a key factor in phonatory prosthesis problems in the context of postlaryngectomy speech rehabilitation …”
Section: Discussionmentioning
confidence: 99%